Aligning profit taxation with value creation - Wolfram F. Richter (Center for Economic Studies and ifo Institute (CESifo), 2019)
The OECD seeks to align transfer pricing and profit taxation with value creation but fails to provide a clear definition. This paper argues that value creation requires international cooperation and that the profit tax base should therefore be allocated according to standards commonly considered as fair when distributing the surplus of cooperation. The claim that current rules of international profit taxation are aligned with value creation is rejected. If anything, the OECD's objective suggests a tax system in which profits are split between the involved jurisdictions. This result triggers the question of possible implementation which is discussed in some detail.
Keywords: H25; F23; M48; 330; international corporate income taxation; intellectual property; value creation; Shapley value; profit splitting